2009
DOI: 10.3945/ajcn.2009.27712
|View full text |Cite
|
Sign up to set email alerts
|

Site-specific concentrations of carotenoids in adipose tissue: relations with dietary and serum carotenoid concentrations in healthy adults

Abstract: Body fat may influence the tissue distribution of carotenoids. Abdominal adipose tissue carotenoid concentrations may be a useful indicator of carotenoid status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
73
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(79 citation statements)
references
References 35 publications
5
73
1
Order By: Relevance
“…In agreement with this assumption, the EURAMIC study [52] showed that men with the highest concentrations of lycopene in adipose tissue had a 48% reduction in the risk of developing a cardiovascular disease compared with men with the lowest lycopene concentrations. Because lycopene is one of the major carotenoids in human adipose tissue [53] and because of its well-known antioxidant properties [12], the protective effect of lycopene on CVD was found to be associated with its antioxidant capacity. However, we have demonstrated here the strong ability of lycopene to prevent inflammation in adipose tissue at a physiological concentration, and this result may be considered a new mechanistic explanation for the association between lycopene and the low prevalence of CVD.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with this assumption, the EURAMIC study [52] showed that men with the highest concentrations of lycopene in adipose tissue had a 48% reduction in the risk of developing a cardiovascular disease compared with men with the lowest lycopene concentrations. Because lycopene is one of the major carotenoids in human adipose tissue [53] and because of its well-known antioxidant properties [12], the protective effect of lycopene on CVD was found to be associated with its antioxidant capacity. However, we have demonstrated here the strong ability of lycopene to prevent inflammation in adipose tissue at a physiological concentration, and this result may be considered a new mechanistic explanation for the association between lycopene and the low prevalence of CVD.…”
Section: Discussionmentioning
confidence: 99%
“…39 Interestingly, abdominal obesity is now considered an important risk factor and predictive indicator for the development of Type 2 diabetes and cardiovascular disease. 40 Waist-to-height AU5 ratio has more recently been shown to have superior discriminatory power for detecting cardiovascular risk factors in both sexes 41 and should be considered as a screening tool for diabetes, hypertension, and CVD in men and women.…”
Section: Discussionmentioning
confidence: 99%
“…Fish and seafood samples were lyophilized before analysis (20 h at À20 8C, 7 bar) as described previously in our analysis of adipose tissue for carotenoids (Chung et al, 2009). Approximately 5 mL methanol was added to an accurately weighed food sample (0.5-1.0 g) in a 50 mL glass vial.…”
Section: Analysis Of Carotenoidsmentioning
confidence: 99%